2023
DOI: 10.3390/metabo13020221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peptaibols Produced by a Marine Strain of the Fungus Trichoderma endophyticum via Mass Spectrometry, Genome Mining and Phylogeny-Based Prediction

Abstract: Trichoderma is recognized as a prolific producer of nonribosomal peptides (NRPs) known as peptaibols, which have remarkable biological properties, such as antimicrobial and anticancer activities, as well as the ability to promote systemic resistance in plants against pathogens. In this study, the sequencing of 11-, 14- and 15-res peptaibols produced by a marine strain of Trichoderma isolated from the ascidian Botrylloides giganteus was performed via liquid chromatography coupled to high-resolution tandem mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…The results clearly support the previous conclusions of other researchers that optimized medium and culture conditions are the main control factors for the production of Paib compounds, as well as its various forms [4,12,14,[48][49][50][51]. We previously found that some emericellipsins produced by E. alkalina exhibited promising antimicrobial activity against a range of Gram-positive bacterial and fungal pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…The results clearly support the previous conclusions of other researchers that optimized medium and culture conditions are the main control factors for the production of Paib compounds, as well as its various forms [4,12,14,[48][49][50][51]. We previously found that some emericellipsins produced by E. alkalina exhibited promising antimicrobial activity against a range of Gram-positive bacterial and fungal pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…Siendo el pepino un histórico modelo vegetal para el estudio de la interacción planta-Trichoderma en donde se ha demostrado su crecimiento asociado a la planta y su capacidad de inducción de respuestas defensivas (Yedidia et al, 1999), a futuro se podrán plantear nuevos experimentos para verificar posible crecimiento endófito de 2IG2102 y las respuestas que en la planta se ejecutan por la presencia de 2IG2102. También hay que considerar que el acetato de etilo pudiera extraer otros sesquiterpenos y peptaiboles, estos últimos son péptidos no ribosomales, algunos de ellos tienen actividad antimicrobiana (Castro et al, 2023) y también pudiera contribuir en la inhibición.…”
Section: Discussionunclassified
“…This information helps identify the exact chemical structure of the NRP, as well as to determine its molecular weight and the presence of various functional groups [107]. Several types of MS techniques can be used for the analysis of NRPs, including matrix-assisted laser desorption/ionization (MALDI-TOF) MS [108], electrospray ionization (ESI) MS [109], and tandem mass spectrometry (MS/MS) [110].…”
mentioning
confidence: 99%